2023
DOI: 10.1088/1361-6528/acca88
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap on thermoelectricity

Abstract: The increasing energy demand and the ever more pressing need for clean technologies of energy conversion 
pose one of the most urgent and complicated issues of our age. Thermoelectricity, namely the direct conversion 
of waste heat into electricity, is a promising technique based on a long-standing physical phenomenon, which 
still has not fully developed its potential, mainly due to the low efficiency of the process. In order to improve the 
thermoelectric performance, a huge e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 247 publications
0
9
0
Order By: Relevance
“…4,5 For instance, much of the energy we produce as a society ends up as high-or low-grade waste heat, which could be recovered since a temperature difference can create electrical power by exploiting the physical phenomenon called thermoelectricity. 8 The thermoelectric conversion efficiency is related to the figure of merit zT = (S 2 σ)T/k of the thermoelectric material used (wherein T is the temperature, k and σ are the thermal and electrical conductivity, respectively, and S is the Seebeck coefficient). 9 Therefore, materials with low thermal conductivity and high Seebeck coefficient, or high thermal voltage, are good candidates for efficient thermoelectric applications.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 For instance, much of the energy we produce as a society ends up as high-or low-grade waste heat, which could be recovered since a temperature difference can create electrical power by exploiting the physical phenomenon called thermoelectricity. 8 The thermoelectric conversion efficiency is related to the figure of merit zT = (S 2 σ)T/k of the thermoelectric material used (wherein T is the temperature, k and σ are the thermal and electrical conductivity, respectively, and S is the Seebeck coefficient). 9 Therefore, materials with low thermal conductivity and high Seebeck coefficient, or high thermal voltage, are good candidates for efficient thermoelectric applications.…”
Section: Introductionmentioning
confidence: 99%
“…While the thermal conductivity was targeted by nanostructuring, which can effectively reduce κ l , the PF was targeted by the complex features that new materials exhibit in their electronic structure. 1,2 These electronic structures typically contain rich features such numerous valleys, 3 warped features, 4 resonant states, 3,5−7 narrow lower-dimensionality threads in three-dimensions (3D), 8 topological states, 9,10 and more (some are included in the descriptors and fitness functions used in machine learning studies). 11−15 Many of these features have been studied in detail in a research direction referred to as "bandstructure engineering", which targets novel transport features and PF enhancement.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thermoelectric generators (TEGs) are solid-state devices that are able to convert the heat flow arising from temperature gradients directly into electricity. , They have the potential to offer a sustainable path for power harvesting and cooling across a variety of industries, including medical, wearable electronics, building monitoring, the Internet of things, refrigeration, thermal management, space missions, transportation, and many more. However, their large-scale exploitation has been limited by the high prices, toxicity, scarcity, and the low efficiencies of prominent thermoelectric (TE) materials.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable materials containing earth-abundant and low-cost elements are the most represented in the collection: among them, binary [1] and multinary [2] chalcogenides, skutterudites [3,4], half-Heusler phases [2,5] and silicides [6].…”
mentioning
confidence: 99%
“…A materials class of rising interest is the one of chalcogenides. In these, a multinary nature has been shown to be a promising strategy to suppress phonon transport [2]. Additionally, ab initio investigations on monolayer SnX 2 (X = S, Se) and Janus SnSSe, revealed that the symmetry breaking in the latter compound can lead to a strongly suppressed thermal conductivity, while maintaining good electronic properties.…”
mentioning
confidence: 99%